Dana Pensiun Syariah - Jasmine Annisa Putri Cahyono; Muhammad Yazid (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Everyone wants to get benefits in old age in order to feel comfortable when they are not actively working and do not earn an income. In the community itself has developed a form of community savings that is increasingly recognized by employees, namely the pension fund. This pension fund program is intended to provide welfare to employees of a company, especially employees who reach retirement age according to the agreement. In this case, pensions can only be given if the employee has entered retirement age or for other reasons so that they obtain the right to receive pension benefits. These policies and programs are expected to be sufficient to encourage balanced growth in terms of supply and demand and strengthen capital, management and human resources (HR) for Sharia Pension Funds. Pension Fund management can be carried out by employers (DPPK) and financial institutions (DPLK). The company has several alternatives. This alternative is adapted to the company's goals without eliminating the rights of its employees. This is very important considering that people still have basic needs that must be met after retirement. With these reserves, when someone enters a less productive period, they still have a source of income.